Corticosteroid responsiveness in patients with acute exacerbation of interstitial lung disease admitted to the emergency department - Hye Jin Jang (Nature Portfolio, 2021)
Abstract Interstitial lung disease (ILD), particularly idiopathic pulmonary fibrosis (IPF), has a poor prognosis. Corticosteroids are widely used in the treatment of acute exacerbation of ILD (AE-ILD). This study aimed to clarify the causes of AE-ILD, determine the efficacy of corticosteroids for treating AE-ILD, and detect differences in the mortality rate among subgroups of ILD. This was an observational retrospective single-center study. Patients with ILD who presented to the emergency department with acute respiratory symptoms from January 1, 2016, to December 31, 2018, were included. Patients with AE-ILD were classified into two groups depending on the prednisolone dose: low dose (0 to 1.0 mg/kg) or high dose (> 1.0 mg/kg). Mortality rates between patients with and without IPF were compared. This study included 182 patients with AE-ILD, including IPF (n = 117) and non-IPF (n = 65). Multivariate Cox regression analysis showed that corticosteroid dose (HR: 0.221, CI: 0.102–0.408, P < 0.001), initial P/F ratio (HR:0.995, CI:0.992–0.999, P = 0.006), and mechanical ventilation within 3 days of hospitalization (HR:4.205, CI:2.059–8.589, P < 0.001) were independent risk factors for mortality in patients with AE-ILD. This study showed that outcomes improve with higher doses of corticosteroids (> 1 mg/kg prednisolone) in patients with AE-non-IPF-ILD. However, this was not the case in patients with AE-IPF.